2013
DOI: 10.1088/0004-637x/764/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Non-Zeeman Circular Polarization of Molecular Rotational Spectral Lines

Abstract: We present measurements of circular polarization from rotational spectral lines of molecular species in Orion KL, most notably 12 CO (J = 2 → 1), obtained at the Caltech Submillimeter Observatory with the Four-Stokes-Parameter Spectra Line Polarimeter. We find levels of polarization of up to 1 to 2% in general, for 12 CO (J = 2 → 1) this level is comparable to that of linear polarization also measured for that line. We present a physical model based on resonant scattering in an attempt to explain our observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 47 publications
7
74
0
Order By: Relevance
“…They concluded that the non-Zeeman CO circular polarization is most probably due to a linear-tocircular polarization conversion, consistent with a physical model based on anisotropic resonant scattering of Houde et al (2013). In fact, it is proposed that background, linearly polarized CO emission interacts with similar foreground molecules aligned with the ambient magnetic field and scatters at a transition frequency.…”
Section: Snr Ic 443mentioning
confidence: 52%
“…They concluded that the non-Zeeman CO circular polarization is most probably due to a linear-tocircular polarization conversion, consistent with a physical model based on anisotropic resonant scattering of Houde et al (2013). In fact, it is proposed that background, linearly polarized CO emission interacts with similar foreground molecules aligned with the ambient magnetic field and scatters at a transition frequency.…”
Section: Snr Ic 443mentioning
confidence: 52%
“…The emerging photons will acquire a phase shift between their orthogonal scattered components, which causes a transformation of linear into circular polarization. Houde et al (2013) showed that this can readily account for the levels of circular polarization reported in their observations.…”
Section: Introductionmentioning
confidence: 78%
“…Houde et al (2013) reported detecting circular polarization in 12 CO (J = 2 → 1) and HNCO (N Ka Kc = 1 1,12 → 1 1,11 ) in Orion KL and proposed a physical model based on anisotropic resonant scattering in an effort to explain these observations. More precisely, they A&A 558, A45 (2013) showed that when the orientation of the magnetic field changes in the path of the propagation of linearly polarized molecular line radiation, the same species of molecules that emitted this incident background radiation will resonantly scatter them in the foreground at their transition frequency.…”
Section: Introductionmentioning
confidence: 99%
“…B-field geometries are generally inferred by preferential emission or absorption by dust or molecules, creating polarized light (e.g., Houde et al 2004Houde et al , 2013Cho & Lazarian 2007). Polarization measurements with molecules require bright lines and are generally restricted to very densesmall-scale structures.…”
Section: Observing Magnetic Fieldsmentioning
confidence: 99%